PERSEPSI SISWA TERHADAP EFEKTIVITAS PROSES BELAJAR MENGAJAR DAN HUBUNGANNYA DENGAN HASIL BELAJAR MATEMATIK - Hasibuan, May Fitriana (Journal of Computer Networks, Architecture and High Performance Computing, 2019)
Mathematics as one part of education that must be learned by each student in formal institutions. Mathematics is also one of the fields of study that has an important role and many of us meet in everyday life. So there is no doubt that mathematics is one of the pinnacles of intellectual glory. Etymologically the perception comes from English, namely "perception" which means response, the power to understand something. Perception can also be interpreted as the process of receiving stimuli where stimuli are in the form of objects, qualities, relationships between symptoms, and events, until the stimulus is realized and understood. The purpose of this study includes obtaining objective data about student perceptions in the learning process of mathematics. Obtain objective data about student learning outcomes and find out the extent to which students' perceptions of the effectiveness of the mathematics teaching and learning process of class VIII SMP Nur Ilmi Percut Sei Tuan. From the results of this study the calculation of the results of the average X ?1 = 60.63 and the standard deviation S1 = 7.09 is taken from the numbers shared with students, and the average X ?2 = 72.44 and standard deviation S2 = 3.88 taken from the average student learning outcomes . The statistics used are significant t test with a significant level of ? = 0.05 and degrees of freedom = 76. Calculations provide tcount = 11.8. By using the tstudent distribution table at a significant level of ? = 0.05 and the degree of freedom = 76 obtained = 2.04. this result shows that tcount> ttable. Thus Ho is rejected and in other words Ha is accepted. The conclusions obtained from data analysis showed that there was a meaningful relationship between the perceptions and effectiveness of students in the learning process of mathematics lessons on students' mathematics learning outcomes.   Keywords: Perception, Effectiveness, Learning Process, Mathematics Learning Outcomes,   Abstrak Matematika sebagai salah satu bagian dari pendidikan yang harus dipelajari oleh setiap peserta didik pada lembaga formal. Matematika juga salah satu bidang studi yang mempunyai peranan penting dan banyak kita jumpai dalam kehidupan sehari-hari. Sehingga tidak diragukan lagi bahwa matematika merupakan salah satu puncak kegemilangan intelektual. Secara etimologi persepsi itu berasal dari bahasa inggris yaitu “perception” yang  artinya tanggapan, daya memahami sesuatu. Persepsi dapat juga diartikan sebagai proses diterimanya rangsangan dimana rangsangan itu berupa objek, kualitas, hubungan antara gejala, maupun peristiwa, sampai rangsangan itu disadari dan dimengerti. Tujuan penelitian ini diantaranya memperoleh data yang objektif tentang persepsi siswa pada proses belajar mengajar matematika. Memperoleh data yang objektif tentang hasil belajar siswa serta mengetahui sejauh mana keterkaiatan persepsi siswa terhadap efektifitas proses belajar mengajar matematika dari siswa kelas VIII SMP Nur Ilmi Percut Sei Tuan. Dari hasil penelitian ini diperoleh perhitungan hasil rata-rata 1=60.63 dan disimpangan baku S1 = 7.09 diambil dari angka yang dibagikan pada siswa, dan rata-rata 2 = 72.44 dan simpangan baku S2 = 3.88 diambil dari rata-rata hasil belajar siswa. Statistika yang digunakan adalah uji t signifikan dengan taraf signifikan ?=0.05 dan derajat kebebasan = 76. Perhitungan memberikan thitung = 11.8. Dengan menggunakan table distribusi tstudent pada taraf signifikan ?=0.05 dan derajat kebebasan = 76 diperoleh = 2.04. hasil ini menunjukkan bahwa thitung > ttabel. Dengan demikian Ho ditolak dan dengan kata lain Ha diterima. Kesimpulan yang diperoleh dari analisis data menunjukkan bahwa ada hubungan yang berarti antar persepsi dan efektivitas siswa pada proses belajar mengajar pelajaran matematika terhadap hasil belajar matematika siswa.   Kata kunci : Persepsi, Efektivitas, Proses Belajar, Hasil Belajar Matematika,